The Role of Segmented Filamentous Bacteria in Immune Barrier Maturation of the Small Intestine at Weaning - Oemcke, Linda A.; Anderson, Rachel C.; Altermann, Eric; Roy, Nicole C.; McNabb, Warren C. (Frontiers in Nutrition, 2021)
The microbiological, physical, chemical, and immunological barriers of the gastrointestinal tract (GIT) begin developing in utero and finish maturing postnatally. Maturation of these barriers is essential for the proper functioning of the GIT. Maturation, particularly of the immunological barrier, involves stimulation by bacteria. Segmented filamentous bacteria (SFB) which are anaerobic, spore-forming commensals have been linked to immune activation. The presence and changes in SFB abundance have been positively correlated to immune markers (cytokines and immunoglobulins) in the rat ileum and stool samples, pre- and post-weaning. The abundance of SFB in infant stool increases from 6 months, peaks around 12 months and plateaus 25 months post-weaning. Changes in SFB abundance at these times correlate positively and negatively with the production of interleukin 17 (IL 17) and immunoglobulin A (IgA) respectively, indicating involvement in immune function and maturation. Additionally, the peak in SFB abundance when a human milk diet was complemented by solid foods hints at a diet effect. SFB genome analysis revealed enzymes involved in metabolic pathways for survival, growth and development, host mucosal attachment and substrate acquisition. This narrative review discusses the current knowledge of SFB and their suggested effects on the small intestine immune system. Referencing the published genomes of rat and mouse SFB, the use of food substrates to modulate SFB abundance is proposed while considering their effects on other microbes. Changes in the immune response caused by the interaction of food substrate with SFB may provide insight into their role in infant immunological barrier maturation.